Heterofunctional Particles as Single Cell Sensors to Capture Secreted Immunoglobulins and Isolate Antigen‐Specific Antibody Secreting Cells. Issue 15 (23rd June 2021) - Ramirez, Katily; Kyu, Shuya; Nguyen, Doan; Han, So‐Yun; Lee, Ye Lim; Bradley, John; Randall, Troy; Sanz, Ignacio; Lee, Frances Eun‐Hyung; Sulchek, Todd
Abstract: Isolating cells based on their secreted proteins remain a challenge. The authors demonstrate a capacity for high throughput single‐cell protein secretion analysis and isolation based on heterofunctional particles combined with fluorescence activated cell sorting (FACS). The workflow shows that antibody secreting cells (ASCs) specific for the H1 protein from influenza virus can be isolated from B cells. The workflow consists of incubating anti‐CD27 particles with the ASCs, capturing locally secreted immunoglobulins with Protein G on the particles, and identifying immunoglobulins specific to H1 via fluorescent labeled antigens followed by FACS to enrich antigen‐specific ASCs. Two particles designs, Janus and mixed, are tested with hybridoma cells. Mixed particles are found to improve antibody collection, while Janus particles are found to bind target cells more effectively. Targeted hybridoma cells in coculture with non‐specific hybridoma cells are identified with a sensitivity of 96% and specificity of 98%. Heterofunctional particles are used to capture ASCs that secrete antibodies specific for influenza virus from B cells from healthy adults isolated from blood after vaccination. Positive H1‐tetramer sorted ASCs are validated using single ASC cultures and identify 23/56 cells specific for H1 demonstrating 164‐fold enrichment from total B cells and 14.6‐fold enrichment from total ASCs. Abstract : A novel process using heterofunctional particles displaying, targeting, and collecting molecules for a high throughput single‐cell protein secretion analysis and isolation protocol compatible with fluorescence‐activated cell sorting is shown. The process is used to identify and collect H1 influenza virus specific antibody‐secreting cells (ASCs) from blood specimens demonstrating an enrichment of 14‐fold from the total ASCs in comparison with ELISpot.